CO-sensing properties of a NASICON-based gas sensor attached with Pt mixed with Bi2O3 as a sensing electrode. (10th February 2015) - Takeda, Hirotaka; Ueda, Taro; Kamada, Kai; Matsuo, Katsuhide; Hyodo, Takeo; Shimizu, Yasuhiro
Abstract: NASICON (Na3 Zr2 Si2 PO12 )-based gas sensors capable of detecting various gases (CO2, NO2, Cl2, VOC and so on) have so far been developed by many researchers. In this study, planar-type gas sensors using a NASICON disc attached with Pt mixed with Bi2 O3 as a sensing electrode (Pt( n Bi2 O3 ), n ( 0.01 ∼ 30 ): the amount of Bi2 O3 addition (wt%)) and Pt as a reference electrode were fabricated, and their sensing properties to CO and H2 were examined in the operating temperature range of 25∼300 °C in dry and wet air. The sensors obtained were denoted as Pt( n Bi2 O3 )/Pt. All Pt( n Bi2 O3 )/Pt sensors fabricated responded to CO at all operating temperatures tested, and the magnitude of CO response increased with a decrease in the operating temperature. In addition, the magnitude of CO response largely depended on the additive amounts of Bi2 O3 to the Pt sensing electrode. The increase in the additive amount of Bi2 O3 to the Pt sensing electrode ( 0.01 ≤ n ≤ 1 ) enhanced markedly the magnitude of CO response, 90% response time and CO selectivity against H2 . The Pt( 1 Bi2 O3 )/Pt sensor showed a linear relationship between the CO response and the logarithm of CO concentration (1∼3000 ppm) in dry air at 25 °C and the CO selectivity against H2 was enhanced in wet air, in comparison with those observed in dry air. The interfacial layer, which was formed between the NASICON and the Pt( 1 Bi2 O3 ) electrode, was suggested to play an important role in improving of the CO-sensing properties.